Intercalation Hosts for Multivalent‐Ion Batteries. Issue 4 (29th December 2022) - Lakhnot, Aniruddha S.; Panchal, Reena A.; Datta, Joy; Mahajani, Varad; Bhimani, Kevin; Jain, Rishabh; Datta, Dibakar; Koratkar, Nikhil
Abstract : Among intercalation, alloying, and conversion battery chemistries, the intercalation chemistry is most widely used in commercial applications due to its superior reversibility, round trip efficiency, and stability, albeit at the expense of reduced specific capacity. While intercalation hosts for monovalent ions (e.g., lithium and sodium) are well developed, the jury is still out on the best available intercalation host materials for multivalent ions such as magnesium, zinc, calcium, and aluminum. In multivalent systems, it is challenging to find electrode materials that can act as a durable host, and accommodate large number of ions, while also permitting fast diffusion kinetics. In this perspective, the electrochemical performance of five distinct class of materials (prussian blue analogues, sodium super ionic conductors, organic, layered, and open‐tunnel oxides) for multivalent ion storage is evaluated. The analysis reveals that open‐tunnel oxides show noticeably superior performance in multivalent ion batteries. Herein, the underlying reasons for this are discussed and the case is made for an in‐depth machine‐learning‐driven "materials exploration effort" directed toward discovery of new open‐tunneled oxides that could lead to vastly superior multivalent ion batteries. Abstract : Herein, in this perspective, the case for open‐tunnel oxides is made as intercalation hosts for multivalent ions. The electrochemical performance of multivalent‐ion chemistries is related to the presence of open‐tunnels (with large‐size pores) in these oxides as well as stability features (such as edge or corner sharing of structural subunits) that enable stable cycling performance.